Efektivitas Terapi Spiritual Emotional Freedom Technique (Seft) Dalam Menurunkan Tingkat Kecemasan Pada Pasien Pre-Operasi - Tsuroya Nabila Musthofa; Dian Hudiyawati (Universitas Malahayati Lampung, 2025)
ABSTRACT Preoperative anxiety is a psychological problem that often arises in patients before undergoing surgery. This anxiety can worsen physical and psychological conditions, and even interfere with the healing process. Non-pharmacological approaches such as the Spiritual Emotional Freedom Technique (SEFT) have been increasingly applied due to their safety and minimal risk of side effects.To determine the effectiveness of SEFT therapy in reducing anxiety levels among preoperative patients through a review of relevant articles. This study employed a scoping review design. The review focused on nursing interventions using the Spiritual Emotional Freedom Technique (SEFT) to reduce preoperative anxiety in patients. Articles were searched using the keywords “SEFT,” “anxiety,” “preoperative,” “nursing intervention,” and “evidence-based practice” across three databases: Scopus, PubMed, and Google Scholar. From a total of 567 articles retrieved, 10 articles met the inclusion criteria after screening titles, abstracts, and full-texts, and were analyzed further. SEFT interventions in the reviewed studies were generally administered for 15–30 minutes per session and conducted 1–3 times prior to surgery, depending on the patient’s condition and the study design.mA review of 10 selected articles showed a significant reduction in anxiety levels following SEFT interventions across various patient groups and types of surgery. Conclusion: SEFT is an effective non-pharmacological therapy to be applied in reducing anxiety among preoperative patients. Keywords: Anxiety, Nursing, Preoperative, Scoping Review, SEFT ABSTRAK Kecemasan pre operasi merupakan masalah psikologis yang sering muncul pada pasien sebelum tindakan pembedahan. Dampak kecemasan ini dapat memperburuk kondisi fisik, psikis, bahkan mengganggu proses penyembuhan. Upaya non-farmakologis seperti Spiritual Emotional Freedom Technique (SEFT) mulai banyak diterapkan karena lebih aman dan minim risiko efek samping. Mengetahui efektivitas terapi SEFT dalam menurunkan tingkat kecemasan pada pasien pre-operasi dengan melakukan kajian literatur. Metode yang digunakan dalam studi ini adalah scoping review. Kajian difokuskan pada intervensi keperawatan menggunakan SEFT untuk menurunkan kecemasan pre-operasi pada pasien. Pencarian artikel dilakukan menggunakan kata kunci “SEFT”, “anxiety”, “preoperative”, “nursing intervention”, dan “evidence based practice” pada tiga basis data, yaitu Scopus, PubMed, dan Google Scholar. Dari total 567 artikel yang diperoleh, setelah melalui seleksi judul, abstrak, dan telaah full-text, sebanyak 10 artikel memenuhi kriteria inklusi dan dianalisis lebih lanjut. Intervensi SEFT pada studi-studi yang direview umumnya diberikan dengan durasi 15–30 menit per sesi dan dilakukan sebanyak 1–3 kali sebelum tindakan operasi, menyesuaikan dengan kondisi pasien dan rancangan studi masing-masing. Dari kajian 10 Artikel yang digunakan menunjukkan adanya penurunan signifikan tingkat kecemasan setelah intervensi SEFT pada berbagai kelompok pasien dan jenis operasi. SEFT merupakan terapi non-farmakologis yang efektif untuk diaplikasikan dalam menurunkan kecemasan pada pasien pra-operasi. Kata Kunci: Kecemasan, Keperawatan, Pra-Operasi, SEFT, Scoping Review